Comparative Analysis of SRAAA, SDSR, SAODV Routing Protocol for Video Streaming in MANET - V.J. Chakravarthy (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The most challenging concern in MANET is video streaming and it essentially exaggerated by these important factors such as fading, node mobility, interference, topology on change in dynamic, collusion, shadowing in multi-path etc. One of the very attractive and considered for many applications is Mobile Ad Hoc Networks (MANET).Routing Protocol is most significant element which is considered as the MANET. Though, the quite demanding task is video streaming over MANET. This paper have been investigated the analysis of routing protocols over MANET for video streaming. The comparison of the three routing protocols are Secure Dynamic Source Routing (SDSR), Secure Ad hoc On-demand Distance Vector (SAODV) and secured Right angled and Ant search routing Protocol (SRAAA) on the basis of various performance metrics such as Throughput, Packet Delivery Ratio (PDR), Delay, Packet Delivery Fraction (PDF), Energy Consumption, Link Failure and Packet Drop has been obtainable in this paper for supporting video streaming applications. Based on the compared stimulated results concluded that SRAAA routing protocol is comparatively better in performance of all metrics than the SAODV and SDSR routing protocols.